Le divorce - Ivory, James; Schiffer, Michael; Merchant, Ismail; Jhabvala, Ruth Prawer, 1927-; Hudson, Kate, 1979-; Watts, Naomi, 1968-; Barr, Jean-Marc, 1960-; Caron, Leslie; Channing, Stockard; Close, Glenn, 1947-; Duris, Romain, 1974-; Fry, Stephen, 1957-; et al. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2003)
A woman travels to Paris to offer help and moral support to her pregnant stepsister who has been left by her French husband.
Based on the novel by Diane Johnson.
Videodisc release of the 2003 motion picture.
Director of photography, Pierre Lhomme ; editor, John David Allen ; music, Richard Robbins.
Kate Hudson, Naomi Watts, Jean-Marc Barr, Leslie Caron, Stockard Channing, Glenn Close, Romain Duris, Stephen Fry, Samuel Labarthe, Thomas Lennon, Thierry Lhermitte.
DVD; Dolby digital.
In English (5.1 surround), French (2.0 surround), or Spanish (2.0 surround) with optional English or Spanish subtitles; closed-captioned for hearing impaired.
Keywords: Feature films; Video recordings for the hearing impaired